Laparoscopic versus open distal pancreatectomy—it’s time to shift our focus and randomize our studies - Beard, Rachel E.; Charpentier, Kevin P. (Laparoscopic Surgery, 2018)
As minimally invasive surgery techniques continue to evolve and are increasingly employed in hepatobiliary and pancreatic surgery, ensuring the non-inferiority of these techniques as compared to the gold-standard of open surgery is paramount.